Internal affairs of political parties and judicial review : an expository study of the experience in Nigeria and Malaysia - Ab Aziz, Shamrahayu; Sambo, A.O. (American-Eurasian Network for Scientific Information (AENSI), Jordan, 2011)
Democracy with calls for constitutionalism has gained more recognition in many parts of the world. Given the general functions of judiciary as one of check and balance mechanisms in democracy most people and government have developed the interest in the judiciary and judicial process. Despite this, the benchmark of academic discourse seems to argue that courts are or should avoid dabbling into internal affairs of the political parties. This article therefore makes an analytical exposition into the attitude of the courts in Nigeria and Malaysia to matters having to do with internal affairs of political parties. The objective is to improve the quality of courts’ decisions and aid law reform in this area of law. It therefore hypothesizes that interference into legal aspects of the affairs of political parties by the court promotes party discipline, democratic principles and reduces injustices across party politics. For the purpose of the analysis, various constitutional provisions and courts decisions from the countries under review are examined.